First Mile Methodologies in Community Informatics Research: Learning from First Nations - McMahon, Rob; Chasle, Arline; Whiteduck, Tim (University of Waterloo Library, 2015)
How can Indigenous research methodologies inform Community Informatics? In this paper we reflect on this question by considering the problematic history of researcher-Indigenous relations before exploring some innovative approaches. Applications of these research tools must emerge during the course of a project to ensure they meet the contexts and needs of community and university partners. Examples from an ongoing research partnership, the First Nations Innovation (FNI) project, show how this ‘First Mile’ work can support Community Informatics research more generally.